Parasites of unionid molluscs (Bivalvia, Unionidae) and their effect on the body of molluscs - O. V. Pavluchenko; T. V. Yermoshyna (Regulatory Mechanisms in Biosystems, 2017)
Among the molluscs of the family Unionidae extensivity of infestation by the helminth Aspidogaster conchicola (Trematoda, Aspidogastridae) is the highest in Unio tumidus and Anodonta anatina, and the lowest – in U. pictorum. The mites of the genus Unionicola (Arachnida, Unionicolidae) occur more often in species of the genus Anodonta and Pseudanodonta complanata than in species of Unio. The larvae of trematodes Bucephalus polymorphus (Trematoda, Bucephalidae) are more often identified in species of the genus Anodonta. The intensity of invasion of molluscs by the helminth A. conchicola was 1.0–5.6 ind./ind. (Unio – 1.0–3.3, Pseudanodonta – 3.0–5.6, Anodonta – 1.3–4.0 ind.), by the water mites Unionicola – 1–69 ind./ind. (Unio, Pseudanodonta – 1–11, Anodonta – 1–69). Due to the influence of aspidogastreans, the cytoplasmic vacuolization and hypertrophy of the cells of the pericardial epithelium and the layer of connective tissue was observed, which leads to a shrinkage of the upper side of the pericardium. Often, there was a nuclear pyknosis and, with deeper violations, their karyorrhexis and karyolysis. In the layer of connective tissue of pericardium of A. anatina encapsulated larvae of aspidogastereans were found. An increase in the cardiac index was observed in molluscs infested by aspidogastreans: the change in the index was the smallest in U. crassus (at 11.5%) and the largest in U. tumidus (at 54.1–61.0%). Smaller cardiac indexes are typical for molluscs with a lower intensity of infestation by aspidogastreans. Moderate intensity of infestation by this helminth (6–10 ind./ind.) caused an increase in the heart rate in molluscs (18.6–29.6%), high intensity (>10 ind./ind.) caused the decreasing of this indicator (14.5–24.0%). At low intensity of the mite (up to 20 individuals) and invasion of the trematode B. polymorphus (minor infections; part of the reproductive glands, populated by parasites, is less than 50%) the acceleration of ciliary beating and increasing of the duration of ciliary beating of the ciliated epithelium (1.4–2.6 times) were observed in species Anodonta and U. pictorum, at high intensity of invasion the inhibition of beating and reduction of the duration of ciliary beating of the ciliated epithelium in these species (45.9–57.4%) was observed. In the case of the general pathological process in the body of molluscs , the influence of parasites can cause the elimination of individuals with high intensity of infestation , which affects the absolute number and population density of molluscs.